Depresión y rendimiento académico en los estudiantes de la Carrera de Medicina Humana de la Universidad Nacional de Loja. - Aulestia Espinosa, José Bolívar (2017)
In the research work: DEPRESSION AND ACADEMIC PERFORMANCE IN THE STUDENTS OF THE HUMAN MEDICINE CAREER OF THE NATIONAL UNIVERSITY OF LOJA, the following general objective was proposed: To establish the relation between depression and academic performance in the students of the third cycle of medicine of The National University of Loja in the period April to September of 2016. Methodologically, it is a descriptive, cross-sectional and Pearson chi-square study; The instrument used was the Beck questionnaire for Depression. The research population was 96 students from the third cycle of the career of Medina Humana, from April to September 2016. After the analysis and with respect to the depression indexes, 67% present ups and downs that are considered normal and their performance fluctuates between 7.56 to 9.19; 21% show mild mood disturbance, with a performance ranging from 7.43 to 9.50; 9% present intermittent depression states with a yield ranging from 7.71 to 8.84; And 3% report moderate depression with academic performance that is between 8.20 and 8.40 out of ten. Regarding academic performance, it is evident that 13% of students investigated failed the cycle while 87% approved it. When applying the Pearson chi box it is determined that depression really impacts significantly on the academic performance of the third cycle students of the Human Medicine Career, which is why it is recommended to the career authorities, within their operational projects annually, including lectures and seminars on depression in college students and their relationship to academic performance. When correlating the levels of depression with academic performance, it is established that of the 12 students failed, 83% have ups and downs that are considered normal; And, 17% manifest mild mood disturbance. Key words: Depression, Academic Performance, Beck's Questionnaire